Implementasi Widgets Builder untuk Monitoring Kinerja Sistem Komputer dengan Menggunakan Rainmeter - Budi Wasito (Jurnal Informatika dan Bisnis, 2021)
The study goal is to create a widget builder application with the feature to generate and import INI files that can be run on the Rainmeter application. The purpose of implementing a widget builder is to assist computer users in making widgets that can be used to monitor system performance. This study refers to the opinion of Sulasno and Rakhmat, which is a monitoring system for the data collection process as well as analyzing the use of limited computer resources such as storage memory, central processing unit, random access memory, and various other computer resources. This study uses a personal extreme programming method that prioritizes delivery speed and a team consisting of one person, data is collected by questionnaire method, observation method and documentation method which has Rainmeter users as respondents. In the widget builder, there are several main features such as an image upload feature, an additional feature for measuring computer resource usage, and a save widget feature. This feature obtained from research conducted by the author is a solution to help Rainmeter users so that widget creation can be done without coding. From the results of the research, it is concluded that the features in the widget builder application that have been implemented have helped Rainmeter users. Keywords: Rainmeter, Widget Builder, System Monitoring, Personal Extreme Programming.